Geochemical evidence of lake environments favorable for the formation of excellent source rocks: A case study from the third member of the Eocene Shahejie Formation in the Qikou Sag, Bohai Bay Basin, eastern China - Zhang, Yongdong; Sun, Yongge; Chen, Jianping (Marine and petroleum geology, 2022)
Lacustrine hydrocarbon source rocks with high quantity and quality of organic matter (OM) are developed within the third member of the Eocene Shahejie formation (Es3) in the Qikou Sag of the Huanghua Depression, Bohai Bay Basin, Eastern China. However, the paleolake environments associated with deposition of these rocks remain relatively undescribed, restricting our understanding of the biogeochemical processes which contributed to the development of excellent source rocks and inhibiting efforts for exploration of lacustrine hydrocarbon deposits. In this study, 18 core samples from the Es3 interval of Well Gangshen 4 in Qikou Sag were subject to a detailed analysis of bulk OM, biomarkers, molecular carbon isotopes, trace elements, and phosphorus (P) to investigate the environment and ecosystem of the ancient lake in which the rocks were deposited. High values of gammacerane index (av. 0.35) recorded in the samples reveals the oxic-anoxic stratification in the water column that persisted for the majority of the year due to the hot climate and great depth of the lake during this period. Meanwhile 13C-depleted hopanes (lower than −63.2‰) indicate an input of OM from chemoautotrophic and methanotrophic bacteria, supported by the production of CO2 and CH4 due to the anaerobic respiration of OM in the hypolimnion or sediments. The abundances of total organic carbon (TOC) relative to total P (TOC/P, mole ratio, av. 289.9) indicates the preferential release of P from sediments in an anoxic environment. However, the low (<2.0) Ni/Co and V/Cr ratios and moderate (av. 1.48) pristane/phytane (Pr/Ph) ratios suggest periodic oxidation of the hypolimnion, which may be a result of replenishment of oxygen during the short-term mixing of the water column driven by seasonal cooling and wind disturbance. Excess P was introduced into the epilimnion via mixing, which initiated high algal productivity after further stratification of the water column. Algal OM produced in this early stratification phase was crucial for the formation of excellent source rocks. The large variation of δ13C in TOC, n-alkanes, and isoprenoids reflects changes in CO2 concentrations or carbon isotopes in the photic zone, which may be attributable to increased inputs of terrestrial OM in response to a changing climate. •Algae provided the crucial OM for developing source rocks in the Es3 member of the Qikou Sag, Bohai Bay Basin.•The development of anoxic bottom water promoted P release from sediments to the overlying water.•Massive input of internal P to the surface water fueled algal productivity.•Excessive input of terrestrial materials diluted OM abundance and deteriorated OM quality.